School Counselor Capacity Building: A Literature Review - Yulizar, Yulizar; Ahman, Ahman; Nurihsan, Juntika; Saripah, Ipah (Jurnal Kajian Bimbingan dan Konseling, 2024)
Capacity describes the human ability to perform, maintain itself, and self-renew. The concept of capacity building is concerned with three distinct levels: the individual, the organizational, and the community level. The literature on capacity building for school counselors is quite diverse. Accordingly, a comprehensive review of the emerging literature is required. This study conducted a systematic literature review exploring the current state of knowledge regarding the capacity building of school counselors. This study was conducted in accordance with the Standard Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P), which guided the selection of 30 articles that met the inclusion criteria. This article delineates the context of school counselor capacity building that has been conducted over the past decade, the research and measurement methods utilized in previous studies, as well as identifies potential formats and contexts for developing school counselor capacity in the future. The findings of this study provide a comprehensive overview of the current state of research in the field of school counselor capacity building and offer insights for future research endeavors.